2017
DOI: 10.1089/gtmb.2016.0324
|View full text |Cite
|
Sign up to set email alerts
|

TCF21 rs12190287 Polymorphisms Are Associated with Ventricular Septal Defects in a Chinese Population

Abstract: Aims: TCF21 knockout mice display cardiac defects, including ventricular septal defects (VSDs). Functional rs12190287 polymorphisms located within the 3¢ untranslated region (3¢-UTR) of TCF21 were associated with a risk of coronary heart disease in the European and Eastern populations. However, whether rs12190287 polymorphisms in the TCF21-3¢UTR confer predisposition to congenital heart disease (CHD) is unclear. Methods: A case-control study was designed consisting of 781 nonsyndromic VSD patients and 867 non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Ventricular septal defect (VSD) is one of the most common types of congenital heart disease. Recent research has shown that allele G at variant rs12190287 is a contributing risk factor for VSD in the Chinese population (Yang et al, 2017). Together, all these data indicated that TCF21 might confer genetic susceptibility to cardiovascular disease.…”
Section: Tcf21 and Other Cardiovascular Diseasementioning
confidence: 86%
“…Ventricular septal defect (VSD) is one of the most common types of congenital heart disease. Recent research has shown that allele G at variant rs12190287 is a contributing risk factor for VSD in the Chinese population (Yang et al, 2017). Together, all these data indicated that TCF21 might confer genetic susceptibility to cardiovascular disease.…”
Section: Tcf21 and Other Cardiovascular Diseasementioning
confidence: 86%
“…While the impact of Tcf21 regulation by microRNAs has not been reported to date during embryonic development, it is important to highlight that several examples of Tcf21-microRNA modulation has been reported in cardiac physiopathological conditions. In Caucasian and East Asian populations, an SNP (rs12190287) in the 3′UTR region of Tcf21 prevents miR-224 binding, resulting in impaired Tcf21 expression, a condition related to the development of alterations in the ventricular septum of the heart [ 218 ]. A deregulation of Tcf21 produced at this SNP has also been associated with the risk of coronary heart disease [ 219 , 220 , 221 ].…”
Section: Post-transcriptional Control Of Proepicardium/epicardium For...mentioning
confidence: 99%
“…According to linkage disequilibrium via Haploview and previous studies, we selected three reported SNPs in TCF21 (rs2327429 T>C, rs2327433 A>G and rs12190287 C>G). 18,22 Circulating leukocytes in patients with 224 PAF patients and 92 controls were collected for DNA extraction by phenol chloroform. We performed genotyping with the selected SNPs in the samples with TaqMan allelic discrimination via ABI 7900HT (Applied Biosystems, Foster City, CA, USA).…”
Section: Snps Selection and Dna Genotypingmentioning
confidence: 99%
“…[15][16][17] Furthermore, TCF21 rs12190287 polymorphisms also conferred predisposition to ventricular septal defects in a Chinese population. 18 Genetic variants could contribute to the AF pathology by affecting the expression and function of proteins responsible for various cellular activities. Therefore, given the marked effect of TCF21 in cardiovascular diseases, we hypothesized that TCF21 may play an important role in the AF pathogenesis.…”
Section: Introductionmentioning
confidence: 99%